Effects of Serum Creatinine Calibration on Estimated Renal Function in African Americans: The Jackson Heart Study. (May 2015) - Wang, Wei; Young, Bessie A.; Fülöp, Tibor; de Boer, Ian H.; Boulware, L. Ebony; Katz, Ronit; Correa, Adolfo; Griswold, Michael E.
Abstract: Background: The calibration to isotope dilution mass spectrometry–traceable creatinine is essential for valid use of the new Chronic Kidney Disease Epidemiology Collaboration equation to estimate the glomerular filtration rate. Methods: For 5, 210 participants in the Jackson Heart Study (JHS), serum creatinine was measured with a multipoint enzymatic spectrophotometric assay at the baseline visit (2000–2004) and remeasured using the Roche enzymatic method, traceable to isotope dilution mass spectrometry in a subset of 206 subjects. The 200 eligible samples (6 were excluded, 1 for failure of the remeasurement and 5 for outliers) were divided into 3 disjoint sets—training, validation and test—to select a calibration model, estimate true errors and assess performance of the final calibration equation. The calibration equation was applied to serum creatinine measurements of 5, 210 participants to estimate glomerular filtration rate and the prevalence of chronic kidney disease (CKD). Results: The selected Deming regression model provided a slope of 0.968 (95% confidence interval [CI], 0.904–1.053) and intercept of −0.0248 (95% CI, −0.0862 to 0.0366) with R 2 value of 0.9527. Calibrated serum creatinine showed high agreement with actual measurements when applying to the unused test set (concordance correlation coefficient 0.934, 95% CI, 0.894–0.960). The baseline prevalence of CKD in the JHS (2000–2004) was 6.30% using calibrated values compared with 8.29% using noncalibrated serum creatinine with the Chronic Kidney Disease Epidemiology Collaboration equation ( P < 0.001). Conclusions: A Deming regression model was chosen to optimally calibrate baseline serum creatinine measurements in the JHS, and the calibrated values provide a lower CKD prevalence estimate.